IPGRI in Europe: Regional report 1999-2000 - International Plant Genetic Resources Institute (2003)
The report highlights some particularly significant achievements of IPGRI's activities in Europe in 1999-2000 and describes the impact that this work is having. IPGRI has a long history of activity in Europe, starting in 1974 when the Institute identified the Mediterranean as an area for priority attention. The early emphasis of the Mediterranean programme was on exploring and collecting crops most threatened by genetic erosion, particularly food legumes, cereals and vegetables. Most of the direct work with Europe's national programmes is concentrated within IPGRI's Regional Office for Europe, based in Rome. This Group is responsible for collaboration with all countries of geographic Europe including Israel, and extending as far east as the Russian Federation and the newly independent states of the former Soviet Union. The activities of the Europe Group cover 54 countries located in the region. IPGRI's focus is on the promotion and development of national and regional strategies for plant genetic resources conservation and use. The Europe Group provides advice to countries needing help in establishing and managing national genetic resources programmes. This includes providing detailed studies on the structure of existing national programmes and recommendations for their improvement. Another key dimension of IPGRI's European strategy is to promote training and the transfer of technology among European institutions and national programmes in developing countries. Past achievements of IPGRI in Europe are detailed in IPGRI's pre-1999 series of Annual Reports.